Pandemic Impact of Covid-19 on Social - Economic Conditions in West Sumatera - Suryani, Yosi; Rinaldy, Rudy (Universitas Negeri Semarang, 2021)
This study aims to determine and analyze the impact of Covid-19 pandemic in terms of socio-economy based on the demographic characteristics of the people in West Sumatra. The data collection method is secondary data, namely data from West Sumatra Provincial BPS and Padang City BPS 2020. Data processing is descriptive quantitative. The discussion of the research analysis is explained in depth and the interpretation of the data is presented in a straightforward and detailed manner in order to produce conclusions containing short answers to the formulation of the problem based on the data that has been collected. The results of the study concluded that there were changes in the socio-economic conditions of the people of West Sumatra according to demographic characteristics due to the Covid-19 pandemic, including the emergence of new habits, workers being temporarily laid off, using restricted public transportation, implementing WFH at work, the service sector being the most affected. As a result of Covid-19, workers in the Wholesale and Retail Trade, Car and Motorcycle Repair, Transportation and Warehousing sectors, as well as the Accommodation and Food and Drink Provision sectors were the most affected, increasing spending and decreasing income.